1995
DOI: 10.1148/radiology.195.3.7753989
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiectasis: comparison of preoperative thin-section CT and pathologic findings in resected specimens.

Abstract: Thin-section CT depicted bronchiectasis in most of the resected bronchiectatic lobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
3
17

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(103 citation statements)
references
References 0 publications
6
77
3
17
Order By: Relevance
“…No relationship was found between the clinical symptoms and disease progression on HRCT scan. This is in agreement with the fact that there is, to date, no satisfactory radiological scoring system for severity and progression of bronchiectasis [28].…”
Section: Discussionsupporting
confidence: 89%
“…No relationship was found between the clinical symptoms and disease progression on HRCT scan. This is in agreement with the fact that there is, to date, no satisfactory radiological scoring system for severity and progression of bronchiectasis [28].…”
Section: Discussionsupporting
confidence: 89%
“…Lynch et al showed that airflow obstruction was common in a majority of his study group (33 patients) [11]. The cause of airflow obstruction, most likely bronchiolitis, secretion, and bronchial hyper-responsiveness [12,13]. Hansel et al [14] studied areas of decreased attenuation using HRCT and concluded that small airway W. A. HASSAN ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…It has a sensitivity of 96% and a specificity of 93% 13. Nevertheless, HRCT has some limitations, including respiratory and cardiac pulsation artefacts, false‐negative reports due to missed focal areas of bronchiectasis between section‐planes, and misinterpretation of bronchial‐artery ratio measurements 11. These limitations have been partially addressed using alternative CT modalities using different imaging algorithms.…”
Section: Diagnostic Approachmentioning
confidence: 99%